(untitled) (NAU Journal of Technology and Vocational Education, 2025)
This study was designed to examine the ameliorative roles of families on women’s empowerment and to assess the effects of empowerment on the economic well-being of women in the area. A descriptive survey research design was adopted, targeting a population of 417 rural women. Using Taro Yamane’s formula for sample size determination, 204 rural women were selected to participate in the study. A structured questionnaire was used as the research instrument, and its reliability was established through a pilot test, which yielded a Cronbach’s alpha of 0.82, confirming internal consistency. Data were analyzed using descriptive statistics and one-way ANOVA at a 0.05 level of significance. The findings revealed that family support significantly enhanced women’s empowerment (F-value = 35.57; p-value < 0.001) and that women’s empowerment, in turn, had a strong positive effect on their economic recovery, including improved income, business stability, and participation in community development (F-value = 78.92; p-value < 0.001). The study concluded that families remain indispensable in the empowerment process, and women’s empowerment contributes meaningfully to their economic well-being in the post-COVID-19 era. It is recommended that families should be encouraged to continue providing financial and emotional support, while policymakers and development stakeholders design family-centered empowerment programs that enhance women’s access to resources and opportunities for long-term resilience.